Fermentation time optimization: Unleashing quality with microbial consortia in whey - Mulyani, Sri; Kamil, Rafli Z.; Permata, Brigitta Indah; Abduh, Setya Budi Muhammad; Al-Baarri, Ahmad Ni’matullah (Asia-Pacific Journal of Science and Technology, 2025)
During cheese production, whey is often produced as a by-product with various nutrients content and can cause damage to the environment when not processed appropriately. To reduce its environmental impacts, it is important to develop various methods for processing, such as lactic acid bacterial (LAB) fermentation by using the nutrients content. Therefore, this study aims to use a mixed LAB culture containing Lactobacillus casei FNCC 0090, Lactobacillus bulgaricus FNCC 0041, and Streptococcus thermophilus 0040 for the production of whey beverages. The experiment was carried out with various incubation times of 0, 2, 4, 6, and 8 hours to determine the effect on the products. The variables examined included total dissolved solids (TDS), viscosity, pH, salinity, whiteness index, and total LAB count using the pour-plated method. Subsequently, a sensory evaluation was conducted to evaluate consumer acceptance. The results showed that LAB count ranged from 7.37 to 8.72 log CFU/ml, pH values 4.85 to 5.59, TDS 9.05 to 7.18 °Brix, and sensory scores 2.82 to 2.92. The increase in LAB count correlated with decreased pH, TDS, and salinity, significantly contributing to increased viscosity. However, the incubation period did not affect the whiteness index of whey beverages. Based on the results, a 4-hour incubation period yielded the most favorable sensory outcomes, meeting both quality standards and production efficiency criteria.